Parental Obligation to Provide Religious Education to Children under Islamic Family Law in Indonesia - Liwayanti, Umi; Zainuri, Muhamad; Nurjamilah, Umi; Rosyadi, Royan (Juwara: Jurnal Wawasan dan Aksara, 2025)
This research aims to examine the obligations of parents in providing religious education to children from the perspective of Islamic family law in Indonesia. Religious education is a basic right of children guaranteed by law, as well as the main responsibility of parents as the first and main educators in the family. Through a normative juridical method with a descriptive-analytical approach, this study analyzes various relevant regulations, such as the Compilation of Islamic Law (KHI), Law Number 1 of 1974 concerning Marriage, and Law Number 35 of 2014 concerning Child Protection. The results of the study show that Islamic family law explicitly obliges parents to instill religious education to children as part of the process of shaping children's morals, morals and character from an early age. The implications of the results of this study indicate that the lack of legal awareness and weak implementation of religious education responsibilities by parents can lead to the formation of a young generation that is spiritually weak and prone to deviant behavior. Thus, strengthening the role of the family in children's religious education is an important aspect in creating a generation of faith, piety and noble character.